Temporality and permanence in Romanian public art - Balko, Maria-Judit (Journal of Education Culture and Society, 2020)
This paper analyzes the relationship between permanent monuments and temporary art projects, as temporality is one of the strategies employed by Romanian artists to counterbalance the support that the Romanian state has shown only towards monuments and memorials dedicated to affirming its value. The complex nature of public art requires a careful consideration of the different dimensions this practice employs, and for that the Western debate on this matter can be a reference point in understanding Romanian public art. We will be looking at possible aspects of the functions of these two main directions in Romanian public art, as they stand methodically one in opposition to the other, in connection with the texts of Piotr Piotrowski (Art and Democracy in Post-communist Europe, 2012) and Boris Groys (Art Power, 2008).